1984
DOI: 10.1007/bf00394178
|View full text |Cite
|
Sign up to set email alerts
|

Dose equivalent commitments from fallout radionuclides in the open waters of the Great Lakes. 1973?1981

Abstract: The levels of (144)Ce, (137)Cs, (125)Sb, and (90)Sr in the open waters of the Great Lakes were measured over the period 1973-81. The levels were found to be very low. (144)Ce was detected only up to 1975 after which it dropped below the detection limit. The data indicate that the concentrations of the remaining three radionuclides have decreased with time. (90)Sr and (137)Cs provide essentially all of the radiological dose from drinking Great Lakes water. The dose equivalant commitments have been calculated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Radioactive Sr was released into the atmosphere between 1945 and 1980 via nuclear weapons testing. While present in Great Lakes water, a 1984 study indicated that radioactive Sr was within safe drinking water parameters (Durham & Joshi, 1984), and it is likely that radioactivity has since decreased. Shaw found increases of Sr from pre-settlement 1952 in their eastern core of Lake Superior associated with mining.…”
Section: Strontiummentioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive Sr was released into the atmosphere between 1945 and 1980 via nuclear weapons testing. While present in Great Lakes water, a 1984 study indicated that radioactive Sr was within safe drinking water parameters (Durham & Joshi, 1984), and it is likely that radioactivity has since decreased. Shaw found increases of Sr from pre-settlement 1952 in their eastern core of Lake Superior associated with mining.…”
Section: Strontiummentioning
confidence: 99%
“…Ce has been suggested as a reference element in the sediment to account for soil influences so that the percentage of actual anthropogenic influx can be measured. Ce has a radioactive isotope, 144 Ce, which is produced in nuclear reactors and was detected in Lakes Superior and Huron in 1974(Durham & Joshi, 1984Tracy & Prantl, 1983). Reavie et al (2005) found paleolimnological Ce concentrations in a Lake George core did not change over the most recent two centuries.…”
Section: Ceriummentioning
confidence: 99%
“…These modern accumulation rates agree with long term rates estimated by pollen analysis of 0.8 to 1 .0 mm yr -' in the areas of thick sediment in southern Lake Michigan and 0 .5 mm yr -1 in the center of the southern basin (King, Lineback, & Gross, 1976) . Durham & Joshi (1984) determined that the lev-els of 137 Cs in Lake Michigan had decreased from 49 .5 pCi m -3 in 1973 to 33 .5 pCi m -3 in 1981 . They attributed the decrease to radioactive decay, reduced input, and physical, chemical, and biological processes .…”
Section: Introductionmentioning
confidence: 99%